Coinfecções HIV/vírus da hepatite B e HIV/vírus da hepatite C no estado de São Paulo, 2007 a 2013 - Kuen Alencar (in memorian), Wong; Suely de Oliveira Farias, Norma; Moraes Coelho, Débora; Zanotti Novaes, Tatiana; Afonso Binelli, Claudia; Tayra, Ângela (BEPA. Boletim Epidemiológico Paulista, 2016)